2018
DOI: 10.1109/tsg.2017.2707345
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Electronic Power Converters in Smart DC Microgrids—An Overview

Abstract: EPCs (Electronic Power Converters) are the key elements of the smart dc microgrid architectures. In order to enhance the controllability of the system, most of the elements are envisioned to be connected to the different buses through EPCs. Therefore, power flow, stability, and dynamic response in the microgrid are function of the behavior of the EPCs and their control loops.Besides, dc microgrids constitute a new paradigm in power distribution systems due to the high variability of their operating conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 76 publications
0
62
0
3
Order By: Relevance
“…More recently, some new strategies have been proposed: to consider the effect of system-level controllers [19,20,27,28], to improve the performance of the model in case strong nonlinearities are present in the system [29], or the first approach towards a blackbox large-signal stability analysis [30]. A review about blackbox modeling structures for DC-DC converters can be found in [31].…”
Section: Blackbox Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, some new strategies have been proposed: to consider the effect of system-level controllers [19,20,27,28], to improve the performance of the model in case strong nonlinearities are present in the system [29], or the first approach towards a blackbox large-signal stability analysis [30]. A review about blackbox modeling structures for DC-DC converters can be found in [31].…”
Section: Blackbox Modelingmentioning
confidence: 99%
“…As mentioned in Section 2, this methodology is based on a weighted combination of small-signal models identified around different operating points. This approach has been successfully applied in DC systems [17,19,20,31], and extended to AC EPCs in [35] at simulation level. Therefore, the present work is the first evidence of a polytopic model applied to represent an actual three-phase DC-AC EPC.…”
Section: Large-signal Analysismentioning
confidence: 99%
“…Small-signal modeling of DC-DC converters has been a subject of research for several decades now, resulting in two main families of modeling techniques: state-space averaging [22] and switch or circuit averaging [39,10]. State-space averaging has become a broadly used modeling approach for DC-DC converters [14], and is considered the most effective method for building small-signal models [43]. It continuously received extensions, for example, for converters in discontinuous conduction mode (DCM) [11,28] or variable-frequency operation [26], and new theoretical results to this day [21].…”
Section: Introductionmentioning
confidence: 99%
“…How to achieve parallel operation, accurate load current sharing between power converters, and maintain stability has become a research hotspot in microgrids [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. With the increasing demand of DC power at load side and the rapid development of distributed DC power sources such as photovoltaic cells, wind power, storage batteries, fuel cells, and supercapacitors, the research on DC microgrids has been gradually increasing in recent years [7][8][9]. Nowadays, DC microgrids have been preliminarily applied in independent power supply systems such as marine power systems, aerospace systems, and data centers [10][11][12].…”
Section: Introductionmentioning
confidence: 99%